Tired Creek Newspapers Folder - Grady County Historical Society (My University, 2009)
This item is a collection of newspapers detailing the Constuction and costs of the dam at Tired Creek. Furthermore, the newspapers detail the plans the county has and the requests for making improvements to the dam. Finally, fishing laws are given as a reminder to lake-goers to make sure that laws are followed.
This item contains 1 PDF and 32 JPG files.
Keywords: Grady County (Ga.); Cairo (Ga.); Newspapers; Tired Creek Lake